The Effect Of Apip Capability On Internal Audit Quality Moderated By Procedural Justice (Case Study At Cilegon City Inspectorate) - Sundari, Afrida; Sanusi, Fauji; Imron , Ali (Advances In Social Humanities Research, 2025)
This study aims to examine the influence of auditor capabilities on the quality of internal audits at the Cilegon City Inspectorate, as well as analyze the role  of Procedural Justice as a moderation variable in this relationship. The stagnation of local government performance assessment through LPPD and SAKIP instruments shows the importance of improving the quality of internal audit as the basis for government performance assessment. The quantitative method was used by involving 162 auditor respondents using a questionnaire, the data was analyzed with Smart PLS. The results showed that auditor capabilities had a positive and significant effect on the quality of internal audits (T-statistics = 4.039; p = 0.000) and Procedural Justice did not show a significant moderation effect (T-statistics = 1.285; p = 0.199). This research strengthens the theory of auditor competence which offers important implications for improving the quality of internal audits in government institutions. Findings related to Procedural Justice provide an opportunity for further research on the role of procedural justice in bureaucratic organizations.